Sustained reductions in migraine days, moderate-to-severe headache days and days with acute medication use for HFEM and CM patients taking fremanezumab: Post-hoc analyses from phase 2 trials. (January 2019) - Halker Singh, Rashmi B; Aycardi, Ernesto; Bigal, Marcelo E; Loupe, Pippa S; McDonald, Mirna; Dodick, David W
Background: In phase 2 and 3 studies, fremanezumab, a monoclonal CGRP antibody, was an effective preventive treatment for high-frequency episodic migraine (HFEM) and chronic migraine (CM). Objective: Post-hoc analyses evaluated population-wise 50%, 75% and 100% responder rates, and the extent to which individual responders sustained a 50%, 75% and 100% reduction in migraine days, moderate-to-severe (M/S) headache days and days of acute medication use during all three treatment months of the fremanezumab phase 2 studies. Design/methods: HFEM patients received either placebo or three once-monthly injections of 225 mg or 675 mg. CM patients received either placebo or three once-monthly injections of 900 mg, or an initial loading dose of 675 mg and subsequent injections of 225 mg. Patients reported headache-related data daily using an electronic diary. Results: In the HFEM study, the percent of patients on fremanezumab doses 225 mg and 675 mg were greater compared to the percent of placebo patients with sustained 50% reduction in migraine days (39% and 35% vs. 10% for placebo, both p  < 0.0001), M/S headache days (36% and 38% vs. 16% placebo, p  = 0.0017 and p  = 0.0007 respectively), and acute medication use days (36% and 27% vs. 8% placebo, p  < 0.0001 and p  = 0.0003). Likewise, although there were fewer patients with sustained 75% reduction, there were increases in the percent of patients on fremanezumab 225 mg and 675 mg in the HFEM study relative to placebo patients in migraine days (19% and 11% vs. 3% placebo, p  = 0.0002 and p  = 0.0176), M/S headache days (19% and 15% vs. 2% placebo, p  = 0.0001 and p  = 0.0011) and days of acute medication use (16% and 8% vs. 2% placebo, p  = 0.0005 and p  = 0.0377). In the CM study, there were increases in the percent of patients on fremanezumab 675/225 mg and 900 mg with 50% sustained reduction in M/S headache days (32% and 40% vs. 15% placebo, p  = 0.0058 and p  = 0.0002) and days of acute medication use (26% and 22% vs. 11% placebo, p  = 0.0098 and p  = 0.0492). There were also increases in the percent of patients on fremanezumab 675/225 mg and 900 mg compared to patients on placebo with 75% sustained reduction in M/S headache days (10% and 13% vs. 3%, p  = 0.0665 and p  = 0.0203). Few patients had 100% sustained reductions in these parameters in either study. Conclusions: Post-hoc results must be interpreted with caution; nonetheless, a statistically significant percentage of patients who initially responded to fremanezumab within 1 month sustained this response over the subsequent 2 months. Sustained reduction in individual patients may provide a novel patient-centric, clinically meaningful endpoint for future trials assessing the effectiveness of preventive migraine treatments. Trials are registered ashttp://clinical trials.gov as NCT02025556 and NCT02021773.